Educating in Social Justice –by it and for it: An Imperiously Ethical Battle - Ileana Castillo-Cedeño (Revista Electrónica Educare)
Indefensibly, we are in a world that has been colonized by global economies and the interests of the market. This makes us think about the urgent need of getting back in touch with the historical and social role of education, thus looking back at the past, valuing the present, and envisioning the future. Indisputably, today we need cognitive and epistemological intelligence and, most of all, spiritual intelligence, the will needed to fiercely struggle to fulfill the ideal and the principle of the educational essence: social justice understood as the direction that inspires us from a deep and generous perspective. This implies estimating the variability and diversity of a world whose framework of relations and correlations make it hard to understand and face. Therefore, not only a deep and critically rigorous look is needed, but also an ontological and axiological basis that help us promote the development of transformations from the ethics of alterity, thus promoting that our reflections, and mainly our actions, allow the understanding required to confront, with genuine courage and intelligence –the one that arises from knowledge, from understanding and being, from doing and coexisting. A vision that involves and warns that no educational process is neutral and, therefore, undergoes the filter of interpretations and subjectivities that occur in the educational environments and that the market logic covers up the different environments and realities where life fluctuates. Based on this, we conclude that it is our civic responsibility, in a global village -with capacity and awareness, to combine expertise, knowledge, and affections in order to rediscover the universal awareness that makes it possible to educate in social justice –by it and for it. This includes the power to interact from writing -based on the legitimacy not only given by a university degree, but also from shared knowledge, from experience in and out of the classroom, and from life itself, which, after all, is the key component of education.